PUASA MELIHAT BULAN VERSUS PUASA MELIHAT DINDING: Telaah Teks dan Konteks Naskah Kitab al-Takwim Walsiyah - Pramono, Pramono (Universitas Lancang Kuning, 2008)
Hisab takwim is one of the elements, learned and applied by the tarekat syatarariah followers. One of the applications of this knowledge is to determine the beginning of Ramadhan which is done by noticing the Ramadhan moon. In Minangkabau, in the 19 century, even untilnow, this idea is still debatable between the tarekat syatariah and other Islamic groups, moreover among the tarekat Syattariyah followers themselves. In the development, the tarekat Syattariyah is called the group of